OTAMAN VOLODYMYR OSKILKO – LEADER OF THE UKRAINIAN LIBERATION MOVEMENT OF THE UNR ERAITS IMPLEMENTATION IN UKRAINE - Holovko, Svitlana; Letkiv, Rostyslav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: a holistic analysis of the socio-political activities of the General-Coroner of the UNR Army Volodymyr Oskilko, clarifying his role in the national liberation struggles of the early 20th century and the formation of Ukrainian statehood. Methods: historical-biographical analysis and historical reconstruction were used to reproduce the key stages of the formation and socio-political activities of the statesman’s personality; the use of the system-functional method made it possible to consider a specific historical figure in the context of political and socio-cultural processes of one of the most important periods in the history of Ukrainian statehood; the method of historical-comparative analogy makes it possible to interpret the results of the study in the context of modern realities. Results: based on the historical-biographical study, the factors of the formation of Volodymyr Oskilko’s personality as a military and public figure of the UNR era were outlined; the activities of Volodymyr Oskilko in the context of the national liberation struggles of the Ukrainian people were analyzed; the role of the outstanding military and public figure is characterized through the prism of the struggle of the Ukrainian people for independence and the restoration of Ukrainian statehood. Discussion: historical experience of statehood in the modern realities of defending independence.